Dietary Betaine and Polyunsaturated Fatty Acids Influence Circulating Fatty Acids and Alpha-Tocopherol in Cats - Jewell, Dennis (Curr Dev Nutr, 2021)
OBJECTIVES: Evaluate the interaction of dietary betaine and two different sources of dietary polyunsaturated fatty acids (PUFA): alpha-linolenate (ALA) and combined eicosapentaenoate (EPA) and docosahexaenoate (DHA) on subsequent circulating single carbon metabolism and metabolomics. METHODS: This study was a complete factorial with or without added betaine and 3 levels of PUFA. Forty eight domestic short hair cats with an average age of 5.8 years (range 1–12) were used in this study. All cats were assigned to a pre-feed period (14 days) and then assigned to one of the six treatment foods: control, control plus 0.35% ALA (flaxseed used to increase ALA), control plus 0.27% EPA&DHA combined (added fish oil as a source), control plus 0.5% betaine, control plus ALA and 0.5% betaine or control plus EPA&DHA and 0.5% betaine. All treatment foods were fed for sixty days. Blood analysis (CBC, chem screens, fatty acid profiles, and metabolome) was completed at the beginning and at the end of the study. Statistical analysis used PUFA source or intake, betaine and interaction with p ≤ 0.05 used as significant. RESULTS: Dietary betaine increased circulating betaine, dimethyl glycine, sarcosine and methionine while adding ALA increased circulating ALA, and EPA&DHA increased their respective circulating concentrations. Betaine increased circulating arachidonic acid when added alone or with ALA with no change when betaine and EPA&DHA were added together. Dietary betaine increased the slope of the linear relationship between circulating EPA (or DHA) to dietary EPA (or DHA). Dietary betaine resulted in an increased concentration of alpha-tocopherol. Similar results were observed with circulating beta- and gamma-tocopherol (combined). CONCLUSIONS: Dietary betaine influences the circulating concentration of polyunsaturated fatty acids and the methyl donor pathway. It also increases circulating tocopherols. FUNDING SOURCES: This study was funded by Hill's Pet Nutrition, Inc.